As Time Goes by: Anxiety Negatively Affects the Perceived Quality of Life in Patients With Type 2 Diabetes of Long Duration - Martino, Gabriella; Catalano, Antonino; Bellone, Federica; Russo, Giuseppina Tiziana; Vicario, Carmelo Mario; Lasco, Antonino; Quattropani, Maria Catena; Morabito, Nunziata (Frontiers in Psychology, 2019)
Introduction: Age-related medical conditions are increasing worldwide. Type 2 Diabetes mellitus (T2DM) represents a chronic disease, which affects a large amount of general population, accounting for over 90% of DM cases. Purpose: As psychopathological symptoms frequently occur in medical conditions, our study aimed at exploring whether psychological factors and metabolic control may affect health related quality of life (HRQoL). Methods: 45 patients with T2DM were consecutively recruited and assessed with a psychodiagnostic battery: Hamilton Anxiety Rating Scale (HAM-A), Beck Depression Inventory II edition (BDI-II) and the 36-Item Short Form Health Survey (SF-36), including indexes Physical and Mental Component Summary (PCS, MCS). Moreover, time since DM diagnosis and glycated hemoglobin (HbA1c) values were detected. Results: Participants (mean age 65.3±5.9 yrs) had a mean time since diagnosis of 11.6±6.7 yrs, and showed a good metabolic control as highlighted by mean HbA1c values 7.1±0.9 %. Median HAM-A score [25(20.7-30.6)], represented high prevalence of anxious symptoms. A moderate expression of depressive symptoms was observed [BDI-II score: 13(8.3-21.4)]. A multiple regression analysis, after correcting for age, BMI, HbA1c value and BDI-II score, showed the perceived quality of life relative to PCS was significantly related to both disease duration (β=-0.55, p=0.03, SE=0.25) and HAM-A scores (β=-0.52, p=0.04, SE=0.24). Moreover, both HAM-A (β=-0.67, p=0.01, SE=0.26) and BDI-II (β=-0.48, p=0.02, SE=0.20) scores were independently predictive of MCS. Metabolic control, instead, was not a significant predictor. Conclusions: Our study suggests a predictive role of both anxiety levels and time since diagnosis in perceived HRQoL in T2DM patients. PCS was associated with anxiety and time since diagnosis and MCS was associated with anxiety and depressive symptoms but not with diabetes duration or metabolic control. These data could be useful to plan T2DM training programs focused on psychological health concerns, possibly leading to a healthy self-management and a better perceived HRQoL, even assisting patients in reducing the negative effect due to the chronicization of T2DM.